THE ROLE OF LAW IN INTERNATIONAL BUSINESS TRANSACTIONS IN THE SETTLEMENT OF INTERNATIONAL DISPUTES - Maria Angela Maharanim Himan (Jurnal Paradigma Hukum Pembangunan, 2025)
International law is the law that governs all activities on an international scale. International law aims to create order and justice in the international community. It also regulates cooperative relations between countries worldwide. The purpose of regulating international relations is to prevent tension and major conflicts between countries. However, what if a country fails to maintain its international relations and even cause disputes between countries, which can lead to various problems? This research uses a normative legal research method, namely by reviewing and collecting information from literature sources such as books and laws.